Implementation of Drug Logistics Management in The Pharmacy Installation of Surya Insani Hospital Pasir Pangaraian Rokan Hulu Regency - Lumbangaol, Sik Fikal; Samran (Jurnal FARMASIMED (JFM), 2024)
Background: The availability of drugs currently creates demand for medical services. Drug logistics management in hospitals includes stages such as planning, procurement, storage, distribution, processing, evaluation and monitoring, and are interdependent on each other so that they must be well coordinated so that each stage can run optimally. Objectives: Knowing the Implementation of Drug Logistics Management in Hospital Pharmacy Installations Surya Insani Research method: Qualitative descriptive research with a cross-sectional approach. Results: In the input  component, There is a positive and significant relationship between training and employee performance. To ensure the quality of supplies and extend the life of equipment, there must be a sufficient budget for purchasing drugs and maintaining drug storage facilities and other related equipment. Guaranteed to be sensitive to measurements and meet requirements, lighting, and calibrate certain equipment annually. In the Process component, planning, procurement, storage, distribution, processing, control. The composition of output, the availability of drugs at the Surya Insani is in accordance with demand, but there are still some drugs that are sometimes not available because the distributor or PBF warehouse runs out of stock. The results of the study also showed that the adequacy of planned drugs and the number of drugs available during the inventory period are important and appropriate when needed. In addition, at the Surya Insani Pasir Pangaraian Hospital. There are still many damaged or expired drugs. This shows that drug management, both input and drug administration processes, still need to be evaluated so that drug management at the Surya Insani Pasir Pangaraian Hospital  can be effective and efficient. Conclusion: The availability of drugs at the Pharmacy Installation of Surya Insani Hospital is in accordance with needs.